2020
DOI: 10.1002/ijfe.2336
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate fluctuations and interest rate policy

Abstract: This research studies the non‐linear relationship between interest rates and exchange rates for China and the United States using the rolling‐window method. We also investigate uncovered interest rate parity (UIP) and the capital market theory for the whole time period and subperiods so as to reconsider various economic connections between China and the United States. The results suggest that the effect of the latter's interest rate adjustment on China/U.S. exchange rate volatility is stronger than that of Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 64 publications
0
16
0
2
Order By: Relevance
“…Empirically, the results of this study are in line with research conducted by Arifin (2003), which shows that interest rates are very effective in strengthening exchange rates. Likewise, with the research of Yung (2021) and Liu and Lee (2020) found that there is an effect of interest rates on the exchange rate. This condition clarifies a need for a measured policy in maintaining the exchange rate during the Covid-19 pandemic because determining the correct interest rate will encourage the strengthening of the exchange rate.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Empirically, the results of this study are in line with research conducted by Arifin (2003), which shows that interest rates are very effective in strengthening exchange rates. Likewise, with the research of Yung (2021) and Liu and Lee (2020) found that there is an effect of interest rates on the exchange rate. This condition clarifies a need for a measured policy in maintaining the exchange rate during the Covid-19 pandemic because determining the correct interest rate will encourage the strengthening of the exchange rate.…”
Section: Resultsmentioning
confidence: 82%
“…However, Yung (2021) found that interest rates also caused exchange rate fluctuations. Liu & Lee (2020) explain the effect of interest rate adjustment on exchange rate volatility in China/the US. Furthermore, changes in the exchange rate of China/US have a slightly more substantial effect on interest rates in the US than on interest rates in China.…”
Section: Introductionmentioning
confidence: 99%
“…Because there is a shortage of export growth, businesses typically cut their output (Rajput, Changotra, Rajput, Gautam, Gollakota, & Arora, 2021). The financial crisis's impact indirectly resulted in a decrease in liquidity, an increase in interest rates, a decrease in commodity prices, a weakening of the exchange rate, and a weakening of growth in sources of funds (Liu & Lee, 2022). This also led to a decrease in consumer, investor and market confidence in various financial companies, which weakened the capital market (Lins, Servaes, & Tamayo, 2019).…”
Section: Asian Economic and Business Developmentmentioning
confidence: 99%
“…In April 2018, the American government imposed additional tariffs of 25 percent on $50 billion worth of commodities imported from China. The Chinese government responded immediately by imposing 25 percent additional duty on the same amount of imports from the United States (for an extensive discussion see Yu and Zhang, 2019;Kwan, 2020;Liu and Lee, 2020).…”
Section: I-introductionmentioning
confidence: 99%